The Utilization Of Cse Mikrobisnis Application Build Via Wordpress In Supporting Small Business - Margareta Sheryl Kurniawan (Journal of Business and Technology, 2023)
An information system is a set of software components that aid in the process of converting raw data into information that is needed by a related party. In utilizing information systems that facilitate work and decision making, its use cannot be separated from the role of technology and the internet. Therefore, information systems are an essential component of any business, organization, or even individual. Technology of information systems offers numerous benefits in the business sector. Particularly when dealing with the rivals by channeling innovations and different ideas purchased on the internet. The same thing happens to entrepreneurial businesses that benefit from technology for their development, even though they started from scratch. Transactions for purchasing products and meals using the CSE Mikrobisnis application via Wordpress, are the example of a technology in information system use for the student business. Before it can be extensively used, it is essential to evaluate the application’s viability and functionality to ensure that users can conduct transactions with confidence.